Rationality of Prayer. - Wieczorek, Krzysztof (Filozofia Chrześcijańska, 2009)
In the paper author argues for the thesis that in confrontation of two kinds of rationality, that is natural cognition of the inherent mind and supernatural cognition in the light of the revealed truth, it is the latter that has the advantage. Then he analyses a prayer (taken as one of the results of the supernatural cognition) as a rational language act and points 5 conditions which seem to be necessary to make the prayer an instrument of shaping a rational attitude towards both God and world.